1960
DOI: 10.2113/gsecongeo.55.2.402
|View full text |Cite
|
Sign up to set email alerts
|

The White Pine copper deposit

Abstract: DISCUSSIONS THE WHITE PINE COPPER DEPOSITSir: Reno Sales (3) has offered a remarkably perceptive discussion of the paper by Wright and myself (6) on the White Pine copper deposit. Ira B. Joralemon has added a brief postscript (2) more or less endorsing Sales' views and calling attention to additional data. My reply can hardly be expected to prove the origin of the deposit, but perhaps it will show how many problems one must overlook or oversimplify to be satisfied with the conclusion that the deposit was forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

1965
1965
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…1) and of the area in which it occurs has been described in a number of papers (White and Wright, 1954, 1960Ensign and others, 1968). Three formations, of upper Keweenawan age, are involved: the Copper Harbor Conglomerate (100-2,000 m thick), Nonesuch Shale (200 m), and Freda Sandstone (3,000-4,000 m), in order of decreasing age.…”
Section: Geologic Setting Of the White Pine Copper Depositmentioning
confidence: 97%
“…1) and of the area in which it occurs has been described in a number of papers (White and Wright, 1954, 1960Ensign and others, 1968). Three formations, of upper Keweenawan age, are involved: the Copper Harbor Conglomerate (100-2,000 m thick), Nonesuch Shale (200 m), and Freda Sandstone (3,000-4,000 m), in order of decreasing age.…”
Section: Geologic Setting Of the White Pine Copper Depositmentioning
confidence: 97%
“…Replacement textures and sulfide zonings indicated that low-temperature cupriferous brines infiltrated fine-grained basal graybeds from coarse-grained footwall redbeds. Disseminated copper sulfides were deposited by replacement of disseminated syndiagenetic pyrite [1][2][3][4][5]. Early semi-quantitative modeling followed, both at the deposit-scale [6,7] and basin-scale [8].…”
Section: Introductionmentioning
confidence: 99%
“…as to the precise age of the hydrocarbons; however, the geologic evidence (White, 1960) favours the viewpoint that the organic matter and the associated copper a r e sedimentary in origin, and contra indicates derivatior of the oil from any other iormaiiwrr. alkanes comes from the independent work of Meinschein and his collaborators which was reported (Meinschein e t al, 1964) simultaneously with our own preliminary announcement (Eglinton et al, 1964).…”
mentioning
confidence: 93%